Evaluation and optimisation of stone matrix asphalt (SMA-13) mix design using weight-matrix method. Issue 4 (1st October 2016) - Ai, Changfa; Qiu, Shi; Xin, Chunfu; Yang, Enhui; Qiu, Yanjun
Abstract : The mix design of the stone matrix asphalt (SMA) mixture is critical to its performance and thereby has attracted considerable attention. In this research, abiding by the principals of orthogonal experimental design, a series of laboratory tests are conducted to assess and optimise the SMA-13 mixture mix designs. Different levels of three critical factors, gradation, asphalt-aggregate ratio, and fibre contents, are applied in the factorial experimental designs. Five performance measures, residual stability, dynamic stability, fatigue lifespan, bending strength, and coefficient of friction, are tested. With the laboratory testing results, weight-matrix analysis is employed to identify the impact of different levels of different factors on overall performance. Based on the results, the influences of the three factors are ranked: gradation, asphalt-aggregate ratio, and fibre contents, from the most influential to the least. Furthermore, analyses are conducted to determine the optimum SMA-13 mix design for four representative climate zones in China. Results are verified with the compared mixture groups.